WEATHER HAZARD CHALLENGES FOR FLYING AGRICULTURAL DRONES IN IRAQ - Saif A. Aljuhaishi; Yaseen K. Al-Timimi; Basim I. Wahab (The Iraqi Journal of Agricultural science)
Deploying drones in agriculture improves resource management and crop monitoring by providing real-time data on insect infestations, plant growth, soil conditions, and irrigation requirements. This study highlights the weather hazards for launching and flying agricultural drones in Iraq. The ten most popular drones for agriculture were chosen, and the weather limitations were determined. Hourly climate data (wind speed, temperature, precipitation, and visibility) in file format NetCDF were used for the period 2004–2023. The Python programming language was used to perform analyses on climate data and calculate the percentage of flight ban frequency due to weather hazards during the study period. Using ArcGIS v.10.8, maps were created of the percentage frequencies of weather hazards for each climate element, as well as for the total elements in Iraq annually and seasonally. The results showed that the worst area for launching and flying agricultural drones in Iraq is the northern region, especially in the winter, spring, and autumn seasons, as the highest percentage of preventing drone flying during the year reached 54.8%, and the percentage was 64.2% in winter, 46.7% in spring, and 51.2% in the autumn. The worst area for launching and flying Don during the summer was in the southern region and reached 40.3%.